ECG simulator - Teng, Samantha Li Si. (2011)
This report will propose an Electrocardiography (ECG) Simulator to provide an alternative education tool for the medical students and engineers working in this field. This paper reports the design and development of an Electrocardiography (ECG) simulator. The signals are obtained from actual subject and through digital signal processing methods; the signal would be decomposed into the required number of coefficients and by using the coefficients generated to reconstruct it back into the time domain. The various methods used are discussed and this report will conclude by discussing the results achieved. Recommendations for future development will be discussed as well. Last but not least, the goal of this report is to allow one to gain more knowledge in signal processing, modelling of the electrocardiography.